2018
DOI: 10.1007/s00029-018-0437-8
|View full text |Cite
|
Sign up to set email alerts
|

Stable Big Bang formation in near-FLRW solutions to the Einstein-scalar field and Einstein-stiff fluid systems

Abstract: We prove a stable singularity formation result, without symmetry assumptions, for solutions to the Einstein-scalar field and Einstein-stiff fluid systems. Our results apply to small perturbations of the spatially flat Friedmann-Lemaître-Robertson-Walker (FLRW) solution with topology (0, ∞)×T 3 . The FLRW solution models a spatially uniform scalar-field/stiff fluid evolving in a spacetime that expands towards the future and that has a "Big Bang" singularity at {0} × T 3 , where its curvature blows up. We place … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(137 citation statements)
references
References 85 publications
14
123
0
Order By: Relevance
“…We first notice that all these Cauchy problems are well-posed. This can be proved using the information provided in [31,32] and with standard arguments incorporating Proposition 5.1. Given this, we proceed to obtain "rough (a-priori) estimates" for solutions of the Cauchy problem which are independent of the value of σ and the particular choice of F .…”
Section: Heuristics Of An Example Problemmentioning
confidence: 95%
See 2 more Smart Citations
“…We first notice that all these Cauchy problems are well-posed. This can be proved using the information provided in [31,32] and with standard arguments incorporating Proposition 5.1. Given this, we proceed to obtain "rough (a-priori) estimates" for solutions of the Cauchy problem which are independent of the value of σ and the particular choice of F .…”
Section: Heuristics Of An Example Problemmentioning
confidence: 95%
“…Investigating these questions for the full Einstein-scalar field system with its large number of degrees of freedom appears out of reach in light of the technical arguments required for the results of [31,32]. The main simplification which we introduce in this paper is therefore to freeze some of the degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where the expressions for the Hamiltonian and momentum constraints (H and M i ) are given by equations (13) and (14). When the generalized Bianchi-identity (37) holds, the evolution equations for the Hamiltonian and momentum constraints are…”
Section: Constraintsmentioning
confidence: 99%
“…A stable singularity formation result for expanding cosmological solutions to the Einstein-scalar field and Einstein-stiff fluid systems was proven in [208] for small perturbations of the spatially flat FLRW solution with topology R × T 3 . It was shown that the basic features of the perturbed solution in the collapsing direction closely resemble those of the FLRW solution, where its curvature blows up at a "big bang" singularity at T 3 , confirming Penrose's strong cosmic censorship hypothesis for the "past-half" of near-FLRW solutions.…”
Section: Cosmological Singularitiesmentioning
confidence: 98%